2022
DOI: 10.1007/s00442-022-05285-7
|View full text |Cite
|
Sign up to set email alerts
|

Honeybees affect floral microbiome composition in a central food source for wild pollinators in boreal ecosystems

Abstract: Basic knowledge on dispersal of microbes in pollinator networks is essential for plant, insect, and microbial ecology. Thorough understanding of the ecological consequences of honeybee farming on these complex plant–pollinator–microbe interactions is a prerequisite for sustainable honeybee keeping. Most research on plant–pollinator–microbe interactions have focused on temperate agricultural systems. Therefore, information on a wild plant that is a seasonal bottleneck for pollinators in cold climate such as Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 110 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…There are several ways microbial volatile organic compounds (MVOCs) are bene cial to plants 23 . It is showed that honeybees affect oral microbiome composition 24 . P. uorescens, P. putida, Corynebacterium sp., Fusarium solani, Byssochlamysfulva, and Penicillium simplicissimum, can degrade eugenol, an antibacterial agent present in clove 33 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several ways microbial volatile organic compounds (MVOCs) are bene cial to plants 23 . It is showed that honeybees affect oral microbiome composition 24 . P. uorescens, P. putida, Corynebacterium sp., Fusarium solani, Byssochlamysfulva, and Penicillium simplicissimum, can degrade eugenol, an antibacterial agent present in clove 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The blueberry nectar microbiome was highly correlated with location. The importance of site-specific factors like the local climate, land cover, flora, and fauna are known to impact microbial community assembly in flowers (Samuni-Blank et al 2014;Aizenberg-Gershtein, Izhaki, Halpern 2017;Vannette et al 2017;Schaeffer et al 2021;Hietaranta, Juottonen, Kytöviita 2023;Schaeffer et al 2023). Floral visitors are particularly significant to the establishment of nectar microbial communities.…”
Section: Effects Of Location On the Nectar Microbiomementioning
confidence: 99%
“…As trees speciated, divergence of inherited microbiomes along phylogenetic lines might be expected. This possibility of microbial inheritance raises further lines of inquiry about species level similarity in different stages of forest succession, and may even beg questions about the potential role of pollinators—a known plant microbiome vector 80 —in shaping tree and wood microbiomes.…”
Section: Introductionmentioning
confidence: 99%